DAMPAK DEFORESTASI TERHADAP KEANEKARAGAMAN HAYATI DAN EKOSISTEM - Nanang Jainuddin (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This study investigates the impacts of deforestation on biodiversity and ecosystems. Through literature analysis and recent research, the intricate relationship between deforestation and changes in species populations, genetic diversity, and ecosystem functions is revealed. Deforestation, as the widespread removal of forests, leads to habitat alterations for various plant and animal species. Habitat loss jeopardizes endemic species and potentially leads to the extinction of species dependent on forests. Habitat fragmentation also occurs due to deforestation, dividing ecosystems into isolated segments. This disrupts species movement and migration, impacting ecosystem dynamics. Bird migration, for example, is disrupted by deforestation, potentially causing population decline and changes in migration behavior. In terms of its ecosystem impact, deforestation disrupts nutrient cycles and alters the climate. Lost forests reduce carbon sequestration, leading to carbon emissions and influencing global climate change. The water cycle is also affected, raising the risk of floods or droughts. Deforestation can lead to soil erosion, mudslides, and disruptions in predator-prey balances. Furthermore, landscape changes due to deforestation can trigger microclimate shifts and disrupt species' adaptation to change. The results of this study indicate that the effects of deforestation are not confined to biodiversity alone but extend to complex ecosystem functions. This research underscores the need for forest preservation and conservation efforts to maintain ecological balance and future sustainability.